BLACK CANADA AND WHY THE ARCHIVAL LOGIC OF MEMORY NEEDS REFORM - Thompson, Cheryl (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2019)
The problem with many archives is that they are searchable only by supplementary metadata (anecdotal data not provided by the original source), rather than secondary metadata (descriptive information that covers dates, origin, history, and cross-referencing); information about a visual object is not always reliable, especially when it comes to Black Canadians. Supplementary metadata in Canadian archives are not classified by race or ethnicity, thus, the very structure of the archive erases from public memory the lived experiences of Black Canadians. Given the move toward digitization over the last fifteen years, the importance of the archive has become a topic of discussion. Since the public can now search through on-line collections, the need to protect and promote material archives has never been more important. This paper will explore the question of the archive-as-subject, rather than archive-as-source, through storytelling. Storytelling is one of the many cultural expressions that have connected Black populations. Using first-person narrative, I give examples from my ten-year-long experience working in Black Canadian archives to probe how the archive can move from its depository role to become a site where memories about Black Canadian experiences across time, space, and place are curated and narrated. What are the ethical challenges around this kind of reform?